High-temperature-resistant and anti-falling synthetic fossil porcelain and preparation method thereof
By preparing a high-temperature and fall-resistant synthetic fossil porcelain composed of kaolin, etc., using intermittent wet ball milling and segmented low-temperature calcination, combined with inkjet printing technology, the problem of using harmful heavy metal dyes and high firing temperatures in existing stone porcelain tableware is solved, and high performance, low cost and environmentally friendly stone porcelain ware production is achieved.
Patent Information
- Application Number
- CN202510024390.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-07
- Publication Date
- 2025-03-21
AI Technical Summary
The existing stone porcelain tableware may use harmful heavy metal dyes during the firing process, and the high firing temperature may have a negative impact on the environment and health. At the same time, the cost of stone porcelain tableware is higher, which limits its widespread use.
It adopts a high-temperature and fall-resistant synthetic fossil porcelain. The raw materials are composed of kaolin, feldspar, cordierite, quartz, alumina, zinc oxide, carbon fiber, aluminum sol and binder. It is prepared by batch wet ball milling, spray drying, segmented low-temperature calcination and other processes, and is decorated with inkjet printing technology.
The stone porcelain ware produced at lower firing temperatures has high damage strength and flexural strength, and does not require the use of harmful heavy metal dyes, which reduces production costs and environmental impacts, while improving the safety and performance of the product.
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of ceramics, and in particular to a high-temperature resistant and drop-resistant synthetic fossil porcelain and a preparation method thereof. Background Art
[0002] Ceramics is the most representative traditional craft in China. The birth of ceramics mainly goes through the processes of raw material refining and purification, embryo forming, bisque firing, glazing, painting and high-temperature firing. The firing temperature of high-temperature firing of ceramics is generally around 1300℃~1380℃. Compared with ceramics, the firing temperature of stoneware tableware is lower, generally around 1290℃.
[0003] However, colored dyes may be used in the production process of stoneware tableware, and these dyes may contain ingredients that are harmful to the human body. During the firing process of stoneware tableware with patterns, heavy metals such as lead and cadmium may be added to "fix the color". These heavy metals may dissolve into food during future use and cause harm to the human body. In order to avoid such problems, inkjet printing technology is now often used for decoration. In addition, the cost of stoneware tableware is cheaper than porcelain, so it is more commonly used in daily necessities, art decorations and various test utensils. Summary of the invention
[0004] In view of the problems existing in the background technology, the present invention provides a high temperature resistant and drop resistant synthetic fossil porcelain and a preparation method thereof, which is achieved through the following technical solutions:
[0005] A high temperature resistant and drop resistant synthetic fossil porcelain, the raw materials are composed of the following parts by mass:
[0006] 35-45 parts of kaolin, 20-25 parts of orthoclase, 8-12 parts of cordierite, 3-10 parts of quartz, 5-10 parts of alumina, 4-8 parts of zinc oxide, 4-8 parts of carbon fiber, 4-7 parts of alumina sol, and 3-6 parts of binder;
[0007] The preparation steps of the high temperature resistant and drop resistant synthetic fossil porcelain are as follows:
[0008] Step a: weigh each raw material according to the number, crush and sieve it, then add water for intermittent wet ball milling, first set the speed to 360 rpm, grind for 15 minutes, then set the speed to 480 rpm, grind for 15 minutes, repeat this speed, and sieve after ball milling for 2 to 3.5 hours to obtain mud;
[0009] Step b: removing moisture from the slurry by spray drying, calcining at 700-900° C. for 2-3 hours, taking out, water quenching, drying, crushing, and passing through a 100-120 mesh sieve;
[0010] Step c: Add the above aggregate and binder into a mixer and mix for 1 hour;
[0011] Step d: placing the above mixture into a mold for compression molding to obtain a green embryo, placing the green embryo at room temperature for 5 to 6 hours, and then drying it at 100° C. for 3 to 4 hours;
[0012] Step e: performing inkjet printing on the dried embryo to draw a pattern;
[0013] Step f: Place the dried green body in a kiln and sinter it at a set sintering temperature. After naturally cooling to room temperature in the kiln, take it out, cut and polish it, and finally obtain stone porcelain.
[0014] Preferably, the binder is a resin.
[0015] Preferably, in step a, the first pass is through a 200-mesh sieve, and after intermittent wet ball milling, the sieve is passed through a 100-150-mesh sieve.
[0016] Preferably, in the intermittent wet ball milling in step a, the ratio of balls: material: water is 1:3:2.
[0017] Preferably, in step e, ceramic inkjet uses ceramic glaze ink.
[0018] Preferably, the sintering conditions in step f are:
[0019] The first stage is calcined in a nitrogen atmosphere at a rate of 10-15°C / min from room temperature to 300-350°C for 1-1.5 hours;
[0020] The second stage is calcined in a nitrogen atmosphere at a rate of 15-20°C / min from 300-350°C to 750-800°C for 4-6 hours;
[0021] The third stage is calcined in a nitrogen atmosphere at a rate of 10-15°C / min from 750-800°C to 950-1050°C for 0.5-1 hour.
[0022] Compared with the prior art, the present invention has the following beneficial effects:
[0023] The optimal raw material ratio obtained by the exploration of the present invention is 38 parts of kaolin, 21 parts of orthoclase, 10 parts of cordierite, 5 parts of quartz, 6 parts of alumina, 4 parts of zinc oxide, 6 parts of carbon fiber, 4 parts of aluminum sol, and 6 parts of resin. The product can withstand a destructive strength of 3852N and a flexural strength of 50MPa. With the increase of the amount of carbon fiber, the product's resistance to falling is enhanced. When the number of raw material components remains unchanged, a slight change in the firing conditions has little effect on the performance of the product. Under high temperature conditions of 1200°C, the temperature of the sample is maintained for 5 hours, and the appearance, dimensional stability, and thermal expansion of the sample are free of cracking and deformation under high temperature conditions. In addition, the intermittent ball milling used in the ball milling of the present invention reduces the production cost caused by the ball mill, and the calcination is a low-temperature calcination with a gradual increase in temperature in a segmented manner, which reduces energy consumption. DETAILED DESCRIPTION
[0024] In order to make the application, technical scheme and advantages of the present invention more clear, the present invention is described in detail in conjunction with specific embodiments. It should be understood that the embodiments are only used to illustrate the present invention, but not to limit the scope of protection of the present invention. All simple improvements to the preparation method of the present invention under the premise of the concept of the present invention belong to the scope of protection of the present invention.
[0025] Embodiment 1;
[0026] Weigh 35 parts of kaolin, 22 parts of orthoclase, 9 parts of cordierite, 10 parts of quartz, 6 parts of alumina, 5 parts of zinc oxide, 4 parts of carbon fiber, and 5 parts of alumina sol; pulverize and pass through a 200-mesh sieve, then add water for intermittent wet ball milling, ball: material: water = 1:3:2, first set the speed to 360 rpm, grind for 15 minutes, then set the speed to 480 rpm, grind for 15 minutes, repeat this speed, ball mill for 3.5 hours and pass through a 150-mesh sieve to obtain a slurry; remove moisture from the slurry by spray drying, calcine at 900°C for 3 hours, take it out, water quench, dry, pulverize, and pass through a 100-mesh sieve; add 4 parts of the above aggregate and resin into a mixing mixer and mix for 1 hour; put the above mixture into The green embryo is pressed in a mold to obtain a green embryo, which is placed at room temperature for 6 hours and then dried at 100°C for 4 hours; the dried embryo is inkjet printed with ceramic glaze ink to draw a pattern; the dried green embryo is placed in a kiln and sintered at a set sintering temperature, and the first stage is calcined in a nitrogen atmosphere at a rate of 10-15°C / min from room temperature to 300-350°C for 1-1.5 hours; the second stage is calcined in a nitrogen atmosphere at a rate of 15-20°C / min from 300-350°C to 750-800°C for 4-6 hours; the third stage is calcined in a nitrogen atmosphere at a rate of 10-15°C / min from 750-800°C to 950-1050°C for 0.5-1 hour. After naturally cooling to room temperature in the furnace, it is taken out, cut and polished, and finally stone porcelain is obtained.
[0027] Embodiment 2;
[0028] Weigh 40 parts of kaolin, 20 parts of orthoclase, 8 parts of cordierite, 5 parts of quartz, 7 parts of alumina, 5 parts of zinc oxide, 5 parts of carbon fiber, and 7 parts of alumina sol; pulverize and pass through a 200-mesh sieve, then add water for intermittent wet ball milling, ball: material: water = 1:3:2, first set the speed to 360 rpm, grind for 15 minutes, then set the speed to 480 rpm, grind for 15 minutes, repeat this speed, ball mill for 3 hours and pass through a 100-mesh sieve to obtain a slurry; remove moisture from the slurry by spray drying, calcine at 700°C for 2 hours, take it out, water quench, dry, pulverize, and pass through a 100-mesh sieve; add 3 parts of the above aggregate and resin into a mixer and mix for 1 hour; put the above mixture into a mold The green embryo is formed by pressing and molding, and the green embryo is placed at room temperature for 5 hours, and then dried at 100°C for 4 hours; the dried embryo is inkjet printed with ceramic glaze ink to draw patterns; the dried green embryo is placed in a kiln and sintered at a set sintering temperature, and the first stage is calcined in a nitrogen atmosphere at a rate of 10-15°C / min from room temperature to 300-350°C for 1-1.5 hours; the second stage is calcined in a nitrogen atmosphere at a rate of 15-20°C / min from 300-350°C to 750-800°C for 4-6 hours; the third stage is calcined in a nitrogen atmosphere at a rate of 10-15°C / min from 750-800°C to 950-1050°C for 0.5-1 hour. After naturally cooling to room temperature in the furnace, it is taken out, cut and polished, and finally stone porcelain is obtained.
[0029] Embodiment 3;
[0030] Weigh 38 parts of kaolin, 21 parts of orthoclase, 10 parts of cordierite, 5 parts of quartz, 6 parts of alumina, 4 parts of zinc oxide, 6 parts of carbon fiber, and 4 parts of alumina sol; pulverize and pass through a 200-mesh sieve, then add water for intermittent wet ball milling, ball: material: water = 1:3:2, first set the speed to 360 rpm, grind for 15 minutes, then set the speed to 480 rpm, grind for 15 minutes, repeat this speed, ball mill for 3.5 hours and pass through a 150-mesh sieve to obtain a slurry; remove moisture from the slurry by spray drying, calcine at 900°C for 3 hours, take out and quench with water, dry, pulverize, and pass through a 120-mesh sieve; add 6 parts of the above aggregate and resin into a mixing mixer and mix for 1 hour; put the above mixture into The green embryo is pressed in a mold to obtain a green embryo, which is placed at room temperature for 6 hours and then dried at 100°C for 4 hours; the dried embryo is inkjet printed with ceramic glaze ink to draw a pattern; the dried green embryo is placed in a kiln and sintered at a set sintering temperature, and the first stage is calcined in a nitrogen atmosphere at a rate of 10-15°C / min from room temperature to 300-350°C for 1-1.5 hours; the second stage is calcined in a nitrogen atmosphere at a rate of 15-20°C / min from 300-350°C to 750-800°C for 4-6 hours; the third stage is calcined in a nitrogen atmosphere at a rate of 10-15°C / min from 750-800°C to 950-1050°C for 0.5-1 hour. After naturally cooling to room temperature in the furnace, it is taken out, cut and polished, and finally stone porcelain is obtained.
[0031] Embodiment 4;
[0032] Weigh 41 parts of kaolin, 20 parts of orthoclase, 9 parts of cordierite, 3 parts of quartz, 5 parts of alumina, 5 parts of zinc oxide, 7 parts of carbon fiber, and 7 parts of alumina sol; crush and sieve through a 200-mesh sieve, then add water for intermittent wet ball milling, ball: material: water = 1:3:2, first set the speed to 360 rpm, grind for 15 minutes, then set the speed to 480 rpm, grind for 15 minutes, repeat this speed, ball mill for 3.5 hours and sieve through a 120-mesh sieve to obtain a slurry; remove moisture from the slurry by spray drying, calcine at 700°C for 2.5 hours, take out and quench with water, dry, crush, and sieve through a 120-mesh sieve; add 3 parts of the above aggregate and resin into a mixer and mix for 1 hour; put the above mixture into The green embryo is pressed in a mold to obtain a green embryo, which is placed at room temperature for 6 hours and then dried at 100°C for 4 hours; the dried embryo is inkjet printed with ceramic glaze ink to draw a pattern; the dried green embryo is placed in a kiln and sintered at a set sintering temperature, and the first stage is calcined in a nitrogen atmosphere at a rate of 10-15°C / min from room temperature to 300-350°C for 1-1.5 hours; the second stage is calcined in a nitrogen atmosphere at a rate of 15-20°C / min from 300-350°C to 750-800°C for 4-6 hours; the third stage is calcined in a nitrogen atmosphere at a rate of 10-15°C / min from 750-800°C to 950-1050°C for 0.5-1 hour. After naturally cooling to room temperature in the furnace, it is taken out, cut and polished, and finally stone porcelain is obtained.
[0033] Embodiment 5;
[0034] Weigh 35 parts of kaolin, 24 parts of orthoclase, 10 parts of cordierite, 7 parts of quartz, 5 parts of alumina, 4 parts of zinc oxide, 8 parts of carbon fiber, and 4 parts of alumina sol; pulverize and pass through a 200-mesh sieve, then add water for intermittent wet ball milling, ball: material: water = 1:3:2, first set the speed to 360 rpm, grind for 15 minutes, then set the speed to 480 rpm, grind for 15 minutes, repeat this speed, and pass through a 100-mesh sieve to obtain a slurry after ball milling for 3 hours; remove moisture from the slurry by spray drying, calcine at 750°C for 3 hours, take it out, water quench, dry, pulverize, and pass through a 120-mesh sieve; add 3 parts of the above aggregate and resin into a mixer and mix for 1 hour; put the above mixture into a mold The green embryo is pressed and formed in a mold to obtain a green embryo, which is placed at room temperature for 6 hours and then dried at 100°C for 4 hours; the dried embryo is inkjet printed with ceramic glaze ink to draw a pattern; the dried green embryo is placed in a kiln and sintered at a set sintering temperature, and the first stage is calcined in a nitrogen atmosphere at a rate of 10-15°C / min from room temperature to 300-350°C for 1-1.5 hours; the second stage is calcined in a nitrogen atmosphere at a rate of 15-20°C / min from 300-350°C to 750-800°C for 4-6 hours; the third stage is calcined in a nitrogen atmosphere at a rate of 10-15°C / min from 750-800°C to 950-1050°C for 0.5-1 hour. After naturally cooling to room temperature in the furnace, it is taken out, cut and polished, and finally stone porcelain is obtained.
[0035] Embodiment 6;
[0036] Weigh 38 parts of kaolin, 21 parts of orthoclase, 10 parts of cordierite, 5 parts of quartz, 6 parts of alumina, 4 parts of zinc oxide, 6 parts of carbon fiber, and 4 parts of alumina sol; pulverize and pass through a 200-mesh sieve, then add water for intermittent wet ball milling, ball: material: water = 1:3:2, first set the speed to 360 rpm, grind for 15 minutes, then set the speed to 480 rpm, grind for 15 minutes, repeat this speed, ball mill for 3.5 hours and pass through a 100-mesh sieve to obtain a slurry; remove moisture from the slurry by spray drying, calcine at 850°C for 3 hours, take it out, water quench, dry, pulverize, and pass through a 100-mesh sieve; add 6 parts of the above aggregate and resin into a mixing mixer and mix for 1 hour; put the above mixture into The green embryo is pressed in a mold to obtain a green embryo, which is placed at room temperature for 5 hours and then dried at 100°C for 3 hours; the dried embryo is inkjet printed with ceramic glaze ink to draw a pattern; the dried green embryo is placed in a kiln and sintered at a set sintering temperature, and the first stage is calcined in a nitrogen atmosphere at a rate of 10-15°C / min from room temperature to 300-350°C for 1-1.5 hours; the second stage is calcined in a nitrogen atmosphere at a rate of 15-20°C / min from 300-350°C to 750-800°C for 4-6 hours; the third stage is calcined in a nitrogen atmosphere at a rate of 10-15°C / min from 750-800°C to 950-1050°C for 0.5-1 hour. After naturally cooling to room temperature in the furnace, it is taken out, cut and polished, and finally stone porcelain is obtained.
[0037] Comparative Example 1;
[0038] The difference between Comparative Example 1 and Example 3 is that the calcination condition is 1050° C. for 6 hours without interruption.
[0039] Comparative Example 2;
[0040] The difference between Comparative Example 2 and Example 3 is that the green body is calcined directly without drying.
[0041] Comparative Example 3;
[0042] The difference between Comparative Example 3 and Example 3 is that the slurry is directly pressed into shape without being spray-dried.
[0043] Performance Testing
[0044] The CKZ-10000 intelligent ceramic tile rupture modulus tester was used to test the destructive strength and flexural strength of the above embodiments and comparative examples.
[0045] The results are shown in Table 1.
[0046] Table 1 Destructive strength and flexural strength test results
[0047] Serial number Destructive strength (N) <![CDATA[Flexural strength( MPa )]]> Example 1 3121 45 Example 2 3365 44 Example 3 3852 50 Example 4 3625 45 Example 5 3508 45 Example 6 3698 47 Comparative Example 1 2965 39 Comparative Example 2 3011 36 Comparative Example 3 2845 38
[0048] It can be seen from the above results that by adjusting the content of each component in the raw material, the performance of the final product obtained is also changing accordingly. When the raw material portions are 38 parts of kaolin, 21 parts of orthoclase, 10 parts of cordierite, 5 parts of quartz, 6 parts of alumina, 4 parts of zinc oxide, 6 parts of carbon fiber, 4 parts of aluminum sol, and 6 parts of resin, the product can withstand a destructive strength of 3852N and a flexural strength of 50MPa. In combination with Examples 1 to 3, it can be seen that the flexural strength and anti-destructive strength of the product gradually increase, and with the increase in the amount of carbon fiber, the product's resistance to falling is enhanced. By comparing Example 6 with Example 3, it is found that the composition of the raw materials remains unchanged, and a slight change in the firing conditions has little effect on the product's anti-fall performance.
[0049] Long-term high temperature stability test
[0050] Under high temperature conditions of 1200°C, the temperature of the sample was maintained for 5 hours, and the performance changes of the sample were observed.
[0051] After 5 hours, the appearance, dimensional stability, and thermal expansion of the samples of Examples 1 to 6 were observed to show that no cracks or deformations were found in the high temperature environment.
[0052] To sum up, the above are only preferred embodiments of the present invention and are not intended to limit the present invention in any form. Any equivalent changes, modifications and evolutions made by technicians familiar with the profession without departing from the scope of the technical solution of the present invention using the disclosed technical content are regarded as equivalent embodiments of the present invention. At the same time, any equivalent changes, modifications and evolutions made to the above embodiments based on the essential technology of the present invention are still within the protection scope of the technical solution of the present invention.
Claims
1. A method for preparing high temperature resistant and drop resistant synthetic fossil porcelain, characterized in that: The method comprises the following preparation steps: Step a: weigh each raw material according to the number, crush and sieve it, then add water for intermittent wet ball milling, first set the speed to 360 rpm, grind for 15 minutes, then set the speed to 480 rpm, grind for 15 minutes, repeat this speed, and sieve after ball milling for 2 to 3.5 hours to obtain mud; Step b: removing moisture from the slurry by spray drying, calcining at 700-900° C. for 2-3 hours, taking out, water quenching, drying, crushing, and passing through a 100-120 mesh sieve; Step c: Add the above aggregate and binder into a mixer and mix for 1 hour; Step d: placing the above mixture into a mold for compression molding to obtain a green embryo, placing the green embryo at room temperature for 5 to 6 hours, and then drying it at 100° C. for 3 to 4 hours; Step e: performing inkjet printing on the dried embryo to draw a pattern; Step f: placing the dried green body in a kiln and sintering it at a set sintering temperature, taking it out after naturally cooling it to room temperature in the kiln, cutting and polishing it, and finally obtaining high temperature resistant and drop-resistant stone porcelain; The raw materials of the high temperature resistant and drop resistant synthetic fossil porcelain are composed of the following parts by mass: 35-45 parts of kaolin, 20-25 parts of orthoclase, 8-12 parts of cordierite, 3-10 parts of quartz, 5-10 parts of alumina, 4-8 parts of zinc oxide, 4-8 parts of carbon fiber, 4-7 parts of aluminum sol, and 3-6 parts of binder.
2. The method for preparing a high temperature resistant and drop resistant synthetic fossil porcelain according to claim 1, characterized in that: In the step a, the first step is to pass through a 200-mesh sieve, and then pass through a 100-150-mesh sieve after intermittent wet ball milling.
3. The method for preparing a high temperature resistant and drop resistant synthetic fossil porcelain according to claim 1, characterized in that: In the intermittent wet ball milling in step a, the ratio of balls: material: water is 1:3:
2.
4. The method for preparing a high temperature resistant and drop resistant synthetic fossil porcelain according to claim 1, characterized in that: In the step e, ceramic inkjet uses ceramic glaze ink.
5. The method for preparing a high temperature resistant and drop resistant synthetic fossil porcelain according to claim 1, characterized in that: The sintering conditions in step f are: The first stage is calcined in a nitrogen atmosphere at a rate of 10-15°C / min from room temperature to 300-350°C for 1-1.5 hours; The second stage is calcined in a nitrogen atmosphere at a rate of 15-20°C / min from 300-350°C to 750-800°C for 4-6 hours; The third stage is calcined in a nitrogen atmosphere at a rate of 10-15°C / min from 750-800°C to 950-1050°C for 0.5-1 hour.
6. The method for preparing a high temperature resistant and drop resistant synthetic fossil porcelain according to claim 1, characterized in that: The binder is resin.